Efficiency in Higher Education: A Review of Research From 1977 to 2022 - Jain, Itisha; Gulati, Rachita (Higher education quarterly, 2025)
ABSTRACT This paper provides a comprehensive survey of studies on the measurement of frontier efficiency in higher education. We review the database of 89 studies assessing higher education efficiency by applying both parametric and non‐parametric methods. For the selection of studies, the Scopus‐indexed journals from 1977 to 2022 are screened and methodically chosen. The analysis presents a classification of research in this area by trends, influential authors and works, emerging issues, primary inputs and outputs, efficiency measurement level, higher education efficiency principles, and estimating methodologies. We note the exponential growth of research on efficiency measurement in higher education from 2011 to 2022. Most evidence is from developed nations like Italy, the UK, China, Australia, and Germany, with more scope for research on higher education in developing nations. The subject analysis reveals that student and departmental investigations need more attention and can lead to groundbreaking research. The survey findings indicate that future researchers should emphasise privatisation, third‐mission activities, social responsibility, and higher education spending.